Nylon Calculus: Relating offensive style to offensive efficiency - Levy, I. (2017)
One of my favorite tools to create over the past few seasons has been my offensive style charts. They are supposed to be a quick snapshot of each team`s offense, evaluated on four stylistic spectra, and separate for any judgements on good or bad.